'Life on hold': The lived experience of radicular symptoms. A qualitative, interpretative inquiry. (February 2019) - Ryan, Clare; Roberts, Lisa
Abstract: Background: Patients with radicular symptoms can experience high levels of pain and disability with at least a third experiencing on-going symptoms 12 months after onset. Aims: To explore 'what matters' about living with radicular symptoms at the point of seeing a spinal specialist and to consider how care can be aligned to best address need. Methods: In this qualitative study, based on the principles of interpretative phenomenological analysis, 14 participants with a clinical presentation of radicular symptoms were purposively recruited from an NHS, Musculoskeletal Service in the UK. Individual, semi-structured interviews were undertaken, audio-recorded and transcribed verbatim. Data were managed using a Framework approach and analysed thematically. Findings: Radicular symptoms were experienced as a protracted journey of acute exacerbations of symptoms that were difficult to make sense of. Adversely affecting almost all aspects of life, participants struggled to maintain their physical and functional independence; their important relationships; social networks and the roles and activities that provided joy and purpose. The impact of radicular symptoms was a 'life on hold' and an uncertain future, and 3/14 reported suicidal thoughts. Conclusions: This paper, the first to focus on the lived experience of radicular symptoms at the point of seeing a spinal specialist, reveals the severity and devastating impact of radicular symptoms. Important implications have been identified regarding the need for clinicians to legitimise the symptoms and impact of radicular symptoms; to identify early those patients who might benefit from injection/surgery; and to signpost appropriate patients to sources of psychological support. Highlights: Radicular symptoms were incapacitating, overwhelming and difficult to make sense of. They adversely affected almost every aspect of everyday life. The impact of radicular symptoms was a 'life on hold' and an uncertain future.